Health Care Disparity and State-Specific Pregnancy-Related Mortality in the United States, 2005–2014. Issue 4 (October 2016) - Moaddab, Amirhossein; Dildy, Gary A.; Brown, Haywood L.; Bateni, Zhoobin H.; Belfort, Michael A.; Sangi-Haghpeykar, Haleh; Clark, Steven L.
Abstract : OBJECTIVE: To investigate factors associated with differential state maternal mortality ratios and to quantitate the contribution of various demographic factors to such variation. METHODS: In a population-level analysis study, we analyzed data from the Centers for Disease Control and Prevention National Center for Health Statistics database and the Detailed Mortality Underlying Cause of Death database (CDC WONDER) that contains mortality and population counts for all U.S. counties. Bivariate correlations between maternal mortality ratio and all maternal demographic, lifestyle, health, and medical service utilization characteristics were calculated. We performed a maximum likelihood factor analysis with varimax rotation retaining variables that were significant ( P <.05) in the univariate analysis to deal with multicollinearity among the existing variables. RESULTS: The United States has experienced a continued increase in maternal mortality ratio since 2007 with rates of 21–22 per 100, 000 live births in 2013 and 2014. This increase in mortality was most dramatic in non-Hispanic black women. There was a significant correlation between state mortality ranking and the percentage of non-Hispanic black women in the delivery population. Cesarean deliveries, unintended births, unmarried status, percentage of non-Hispanic black deliveries, and four or less prenatal visits were significantly ( P <.05) associated with increased maternal mortality ratio. CONCLUSION: Interstate differences in maternal mortality ratios largely reflect a different proportion of non-Hispanic black or unmarried patients with unplanned pregnancies. Racial disparities in health care availability, access, or utilization by underserved populations are an important issue faced by states in seeking to decrease maternal mortality. Abstract : Interstate differences in maternal mortality ratios largely reflect a different proportion of non-Hispanic black or unmarried patients with unplanned pregnancies.Supplemental Digital Content is Available in the Text.